Campaña de lanzamiento de avena instantánea “Thani” - Veliz Martínez, Anabel Andrea (2021)
The following work aims to develop a launch campaign for a new instant oatmeal brand for a transnational company that wants to enter the Peruvian cereal market. To develop the creative and media strategy, the market and target audience were investigated, men and women aged 20 to 35 from socio-economic level A and B. With the results, the brand name, logo and product packaging were developed, the creative concept that is going to be present during the first years of exposure and media strategy. All the pieces made are intended to publicize the new brand, its differential characteristics and points of sale. In addition, it tries to identify with its audience and give them a solution tailored to their nutritional and practical needs.